Innovative methods food wholesalers in Iceland use to reduce food waste - Hlynur Rafn Guðmundsson 1995- (2021)
Purpose: This research aims to discover what radical innovation methods food wholesalers in Iceland are using to reduce food waste, as well as what barriers and incentives they face when incorporating the circular economy, and whether they are working purposefully to achieve the United Nations Sustainable Development Goal 12.3. Methodology: This research is based on a qualitative study that included in-depth interviews with six key players in Iceland's food wholesale market. The interviews were semi-structured, with an interviewer and a questionnaire with open-ended questions. Findings: The findings from the study indicate that food wholesalers in Iceland use a wide range of methods to reduce food waste at every level of the food waste hierarchy. According to the findings, the methods used by Icelandic food wholesalers to reduce food waste are primarily classified as incremental innovation. Food wholesalers encountered organizational barriers when attempting to reduce food waste and incorporate the circular economy. The primary incentive to reduce food waste and incorporate the circular economy was financial. Most of Iceland's food wholesalers are not actively pursuing the UNSDGs, which lessens the odds of reaching them. Limitations: The study's main limitation was the interviewees' lack of knowledge about the circular economy. Because the interviewees' knowledge of the circular economy was limited, the open-ended questions asked in the interview most likely influenced the results. Originality/Value: This study is unique because it examines the methods food wholesalers in Iceland use to reduce food waste and incorporate the circular economy. The research for this study adds to the literature in innovation, food waste, the circular economy, and the United Nations Sustainable Development Goals. The research creates practical knowledge for managers in the food wholesaler sector and managers in other links in the food value chain. Keywords: Food waste, Innovation, Circular Economy, UN Sustainable development goals